Coordination - Johannessen, Janne Bondi 1960- (Oxford Univ. Press, 1998)
This study marks the first occasion that a cross-linguistic approach has been taken to systematically focus on the subject of coordination in the field of grammar. Dr Johannessen's ideas are broadly in line with those of Chomsky.
Keywords: Nevenschikking; Grammatik; Grammar, Comparative and general -- Coordinate constructions; Koordination -- Linguistik; Hochschulschrift